Immunological features of a lung cancer patient achieving an objective response with anti‐programmed death‐1 blockade therapy - Kamata, Toshiko (Cancer Sci, 2019)
The role of immune checkpoint inhibitors in metastatic lung cancer has been established in recent years and the pretherapeutic profiles of the tumor microenvironment in responders have been increasingly reported. The role of salvage surgery and the immune profiles of the posttherapeutic specimens in patients achieving an objective response have rarely been studied. We report a case of metastatic lung cancer treated by anti‐programmed death‐1 Ab followed by surgical resection. The immune status of the tumor was assessed, showing germinal center formation, memory B cell infiltration, and a high frequency of interferon gamma ‐secreting T cells.